Flower petals fall, but the flower endures the Japanese philosophy of transience - Takeuchi, Seiichi 1946- (Japan library (Shuppan Bunka Sangyō Shinkō Zaidan, 2015)
"Life is short and transient--Japanese people call this sentiment mujokan. However, what if we could sweep away the "despair" looming over the present age by proactively accepting this mujo (transience)? Perusing the thought of mujo from the perspectives of philosophy, literature, art and religion, Takeuchi delves into the view of life and death unique to the Japanese people who have shared "grief" and "pain" with each other, as well as into the very core of their underlying spirit."-- Provided by publisher.